Environmental Capabilities and Environmental Innovations of Manufacturing Firms in Malaysia - Tze San Ong; Ah Suat Lee; Boon Heng Teh; Hussain Bakhsh Magsi; Sin Huei Ng (Indonesian Journal of Sustainability Accounting and Management, 2020)
The popularity of achieving environmental sustainability among businesses is not exceptional in the green business literature. However, despite its popularity, businesses are still practically clueless about its benefits. This study employs the dynamic capabilities theory to investigate the relationship between environmental capabilities (i.e., environmental strategic focus, shared vision, management support, collaboration, and technological capabilities) and environmental innovation. To test the hypotheses, data from a sample of 124 firms were collected from managers of environmental management system 14001-certified Malaysian manufacturing firms. The collected data were analyzed using structural equation modeling with partial least squares version 3.0. The results indicated that environmental technological capabilities and environmental collaboration both have a positive impact in directly enhancing the firms' environmental innovations. The findings of this study indicate the possibility that manufacturers can remain competitive by integrating environmental considerations at the strategic level; collaborating with suppliers, customers, and the local community for environmental solutions; and investing in environmental technological capabilities.